2021
DOI: 10.12659/msm.933275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Post-Mastectomy Radiation Therapy for Sentinel Lymph Node Micrometastases in Early-Stage Breast Cancer Patients

Abstract: Background The association of radiotherapy with breast cancer survival in patients who underwent a mastectomy and had micrometastases in the sentinel lymph node is unclear. Material/Methods The survival benefit of radiotherapy was examined in patients with T0/1-T2N1mi breast cancer undergoing mastectomy plus sentinel lymph node biopsy (SLNB). Kaplan-Meier curves were employed for survival analysis and competing risk analysis, and a propensity score matching (PSM) cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Similar to most other nomograms for the prediction of axillary nodal status, it does not consider the size of the metastatic deposit. Previous trials have failed to prove any benefit of PMRT for patients with only micrometastatic deposit (≤2.0 mm) 42, 43 and micrometastatic disease is not included in the current guidelines concerning recommendations for PMRT 1214 . Therefore, the presented Nomogram I was developed to predict ≥1 macro-SLNMs specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to most other nomograms for the prediction of axillary nodal status, it does not consider the size of the metastatic deposit. Previous trials have failed to prove any benefit of PMRT for patients with only micrometastatic deposit (≤2.0 mm) 42, 43 and micrometastatic disease is not included in the current guidelines concerning recommendations for PMRT 1214 . Therefore, the presented Nomogram I was developed to predict ≥1 macro-SLNMs specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary to the IBCSG 23–01 trial, our meta‐analysis demonstrated no OS difference when performing ALND in mastectomy patients with micrometastatic SLNs. Due to the minimal nodal burden and a low risk of NSLNM, patients with nodal micrometastases undergoing mastectomy are likely to be treated adequately with SLND only without ALND [22, 42].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the question of whether complete ALND is actually required for patients with micrometastasis is an important one because of the long-term prognostic risk of systemic recurrence and local failure associated with residual axillary disease in sentinel lymph node positive patients who elect not to have further axillary surgery, and Controversy still exists surrounding the best management of patients with SLN micrometastases, in terms of further axillary surgery or radiotherapy and/or systemic adjuvant treatment ( 3 , 8 , 36 ). Nevertheless, we were surprised to find that axillary treatment was not an independent factor affecting OS and BCSS, nor was radiotherapy, although many people supposed that ALND and axillary radiotherapy could be alternatives for patients with SLN micrometastases since they may reduce loco-regional recurrence ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the relative reduction in the number of ALNDs performed over the last decade is supported by a large and growing evidence base ( 3 , 17 , 19 ). In addition, in view of the fact that micrometastases are likely to represent a lower risk of local and distant failure than macrometastases and that women could be spared the morbidity of ALND, at present further intervention for women with SLN micrometastases is primarily surgical treatment, rather than axillary radiotherapy ( 3 , 36 ). Additionally, since SLN micrometastases are most commonly confirmed following complete pathological assessment, any further axillary surgery needs to take place on a second occasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation